Enhancement of Biocrude Quality Using Fecal Sludge and Organic Solid Waste Through Two-Stage Hydrothermal Liquefaction Technique - Adnan, H M Fairooz; Fayshal, Md Atik; Chowdhury, Dipa Roy; Jemi, Tamanna Sharif; Pantho, Nafis Ahmed; Khalekuzzaman, Md (Journal of Engineering Science, 2024)
The escalating global challenge of managing unmanaged fecal sludge (250-300 million tonnes/year) and organic solid waste (600-700 million tonnes/year) necessitates innovative and sustainable waste-to-energy solutions. Hydrothermal liquefaction (HTL) of FS & OSW to produce biocrude has been seen as a double-edged sword to substitute fossil fuel and address the issues relating to unmanaged waste (GHG emission, global warming, climate change). Through this study, an approach was taken to improve the biocrude production and enhance the biocrude quality by introducing a two-stage heating in HTL of FS and OSW separately. Four different runs were comprised in this study where one run was in conventional one stage, at 320℃ for 60 min. In terms of the other three runs, in the first stage, 100, 200, and 300℃ were retained for 30 min respectively and the second stage was conducted at 320℃ for 30 min. Results indicate a substantial improvement in biocrude yield of 15% &18% through two-stage heating during HTL (30 min at 200℃, and then 30 min at 320℃) compared to conventional single-stage HTL processes of FS & OSW respectively with a biomass conversion rate of 70%. From the analysis of biocrude maturity & intensity of oil we observe a high potential for crude oil formation being classified as Kerogen type I. GC-FID shows that increasing heat in the first stage tends to produce a lighter fraction (at 300℃ in the first stage produces biocrude with a lighter fraction>80% from FS & OSW feedstocks) in biocrude. In addition to improving the overall efficiency of converting organic waste to biocrude, the two-stage system offers a more flexible platform that allows the biofuel composition to be customized to match the needs of individual applications. The results show that a two-stage HTL process is a feasible and effective technique for converting difficult waste streams into biofuels, with implications for both environmental sustainability and energy security. Journal of Engineering Science 15(1), 2024, 95-105